Beyond Firm Age: Corporate Governance, CSR, and Operational Scale as Financial Performance Drivers - Elyn Rachmawati; Nur Handayani (Journal of Accounting Science, 2026)
General Background: Balancing profit with responsibility remains a fundamental challenge for resource-intensive industries worldwide. Specific Background: In Indonesia’s mining and energy sectors, post-pandemic shifts in commodities, evolving regulations and rising ESG expectations have made Corporate Governance (CG), CSR and operational scale (SOP) crucial factors for long-term sustainability. Knowledge Gap: Previous research has examined CG, CSR, SOP and the company’s operational age (MOP) in isolation, leaving a gap in our understanding of how these factors interact within Indonesia’s extractive industries. Objective: This study examines the simultaneous effects of CG, CSR and SOP on financial performance and assesses the moderating role of MOP amongst mining and energy companies listed on the IDX from 2019 to 2023. Methods: Moderated regression analysis was applied to panel data from 62 mining and energy companies listed on the IDX over the period 2019–2023. Results: CG, CSR and SOP each significantly improved financial performance, whilst MOP did not exhibit a moderating effect. Novelty: This study regards a zero-moderation effect as a significant finding, which calls into question the application of organisational life-cycle theory in Indonesia’s extractive sector in the post-pandemic era. Implications: Strong governance and CSR drive financial performance regardless of a company’s age, thereby encouraging early ESG investment and the consistent pursuit of sustainability.